Sexual and reproductive health challenges among street adolescents in Sylhet city, Bangladesh: A cross-sectional study - Yeahyea Ahmed; Md Abdullah Saeed Khan; Laila Afroz; Mohammad Nurunnabi; Md Golam Abbas (PLoS ONE, 2026)
Background Street adolescents often engage in early sexual activity, have multiple partners, and are at high risk of sexual abuse and exploitation. Despite the significance of this issue, there is a critical gap in understanding the sexual and reproductive health (SRH) needs, practices, and challenges of this marginalized population in Bangladesh, which this study aimed to explore. Methods A cross-sectional study was conducted from August to December 2023, involving 311 street adolescents aged 16–19 years in Sylhet City Corporation, Bangladesh. Data were collected through face-to-face interviews using a semi-structured questionnaire. The questionnaire covered sociodemographic characteristics, pubertal changes, SRH status, and SRH-seeking behaviors. Results Of all participants, 62.8% were males and 37.2% were females, with a mean age of approximately 17.3 years for both sexes. Sexual intercourse was reported by 32.56% of participants, with a significant gender disparity (76.79% females vs. 6.35% males, p < 0.001). Contraceptive use was low at 14.14%, primarily condoms. Among female participants who ever had sex, 81.13% reported pregnancy, with 50.67% having had an abortion. Knowledge of sexually transmitted diseases (STDs) was alarmingly low, with only 2.33% aware of transmission methods. Less than half (45.97%) of participants utilized SRH services. Sexual abuse was reported by 61.79% of participants. Logistic regression revealed that younger age (Adjusted Odds Ratio [AOR]: 0.62, 95% CI: 0.48–0.79), being female (AOR: 9.10, 95% CI: 3.58–25.3) and longer duration of stay on the streets (AOR: 1.14, 95% CI: 1.02 to 1.27) were associated with higher odds of experiencing sexual abuse. Conclusion Street adolescents in Sylhet City face severe SRH challenges, including high rates of sexual abuse, low contraceptive use, and limited STD knowledge, with significant gender disparities, which should be addressed through appropriate and urgent interventions.